Appositeness of Teacher Training for In-Service EFL Teachers in Real Teaching Context (Journal of NELTA, 2016)
There are various ways for EFL teachers to grow professionally. Attending workshops and training programs are believed to foster their upward mobility. At the same time, different teachers come up with numerous challenges in their classroom with the change of time. So, the learning they had in their college and university level may not always help them to dissolve all the problems in their diverse classroom settings. In this context, this small-scale study is explores whether the insights teachers get from the workshops and the trainings conducted by Nepal English Language Teachers’ Association (NELTA) are applicable and they contribute to liquefy the challenges EFL teachers face in their classroom. Drawing on the findings of this study and the support from the literature, it has been justified that training programs help teachers to grow professionally, but they can hardly apply the knowledge and skills they learn in their real classroom situations. With the help of data collected through the interview, it is crystallized that trainings have been almost unsuccessful to help the teachers cope with ever changing professional world. Journal of NELTA, Vol. 21, No. 1-2, 2016, Page:121-127